Preface - Nikoletta Hendrik (Elpis)
In March 2017, we dedicated a week of enthusiasm to Stoic philosophy by hosting the first Hungarian version of Stoic Week, inspired by the original idea of Stoicon. Our aim was to introduce Stoicism to a wider audience with no prior philosophical education but an interest in the modern renaissance of the movement on the one hand, and to generate in-depth scholarly discussions of classical texts and the afterlife of the Portico on the other. The week consisted of four separate events: firstly, we visited the Aquincum Museum, where the guided tour offered us a glimpse of Marcus Aurelius’ life in Pannonia. Secondly, we had a public reading of selected texts from Seneca and Epictetus, which happened under the title “the unconquerable power of the soul”. These were followed by an academic workshop in Hungarian on Plutarch’s On Stoic Self-Contradictions, and the week culminated in a final two-day international event, The Stoic Tradition Conference. We had the pleasure of attending John Sellars’ opening keynote speech and altogether eleven talks covering the reception of Stoicism by Cicero, Seneca, Alexander of Aphrodisias, Plotinus, Irenaeus, Lactantius, Lipsius, Spinoza, Deleuze and Frankfurt. This volume contains selected and peer-reviewed papers of the conference.